Implementasi Program Sidang Esai sebagai Strategi Pengembangan Pemahaman Literasi Siswa di SMP Swasta IT Ad-Durrah Marelan - Malikul Sholeh As-Salim; Misywar Rasyid (CV Global Research Publication, 2026)
This study was motivated by the limited development of students’ literacy, which extends beyond basic reading and writing skills to include critical thinking, argumentation, and academic communication of ideas. This study aims to analyze the implementation of the Essay Defense Program as a strategy for developing students’ literacy at SMP Swasta IT Ad-Durrah Marelan. Employing a qualitative approach with a case study design, data were collected through participatory observation, in-depth interviews, and document analysis involving school representatives and ninth-grade students. The findings indicate that the Essay Defense Program develops literacy through stages of topic selection, simple research activities, writing guidance, revision, and academic presentations. The program enhances students’ writing quality, reading comprehension, confidence in presenting arguments, critical thinking skills, and holistic understanding of learning materials. Furthermore, the program integrates Islamic values, including honesty (ṣidq), responsibility (amanah), and academic ethics. The findings demonstrate that value-based pedagogical strategies can foster multidimensional literacy and strengthen students’ academic character.